Management of Acute Decompensated Heart Failure in Rural Versus Metropolitan Settings: An Australian Experience - Chan, R.K.; Dinh, D.T.; Hare, D.L.; Lockwood, S.; Neil, C.; Prior, David; Brennan, A.; Lefkovits, J.; Carruthers, H.; Reid, Christopher; Driscoll, A. (ELSEVIER SCIENCE INC, 2022)
Background: Acute decompensated heart failure (ADHF) is the most common cause of hospital admission in patients over 65, with poorer outcomes demonstrated in rural versus metropolitan areas. The aim of this study was to compare the in-hospital and post-discharge management of ADHF patients admitted to rural versus metropolitan hospitals in Victoria. Methods: Data from the Victorian Cardiac Outcomes Registry, Heart Failure (VCOR-HF) project was used. This was a prospective, observational, non-randomised study of consecutive patients admitted to participating hospitals in Victoria, Australia, with ADHF as their primary diagnosis over four 30-day periods during consecutive years. All patients were followed up for 30 days post discharge. Results: 1,357 patients (1,260 metropolitan, 97 rural) were admitted to study hospitals with ADHF during the study periods. Cohorts were similar in age (average 76.87±13.12 yrs) and percentage of male gender (56.4% overall). Metropolitan patients were more likely to have diabetes (44.4% vs 34.0%, p=0.046), kidney disease (65.8% vs 37.1%, p<0.01) and anaemia (31.9% vs 19.6%, p=0.01). There was no significant difference in length of stay between metropolitan and rural patients (7.49 vs 6.37 days, p=0.12). There was no significant difference between metropolitan and rural patients in 30-day rehospitalisations (19.1% vs 11.6%, p=0.07, respectively) and all-cause 30-day mortality (8.2% vs 4.1%, p=0.15, respectively). Metropolitan patients were significantly more likely to have seen their general practitioner (GP) (68.1% vs 53.2%, p<0.01) or attend an outpatient clinic (35.9% vs 10.6%, p<0.01) by 30 days. There was no significant difference in number of days to follow-up of any kind between groups. Referrals to a heart failure home visiting program remained low overall (19.9%). Conclusion: There was no significant difference in 30-day rehospitalisations or mortality between patients admitted to rural versus metropolitan hospitals. Geographical discrepancies were noted in follow-up by 30 days, with significantly more metropolitan patients having seen a doctor by 30 days post-discharge. Overall follow-up rates remain suboptimal.